2022
DOI: 10.1111/1462-2920.16218
|View full text |Cite
|
Sign up to set email alerts
|

Summer thaw duration is a strong predictor of the soil microbiome and its response to permafrost thaw in arctic tundra

Abstract: Climate warming has increased permafrost thaw in arctic tundra and extended the duration of annual thaw (number of thaw days in summer) along soil profiles. Predicting the microbial response to permafrost thaw depends largely on knowing how increased thaw duration affects the composition of the soil microbiome. Here, we determined soil microbiome composition from the annually thawed surface active layer down through permafrost from two tundra types at each of three sites on the North Slope of Alaska, USA. Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Bacterial predators and particularly Myxococcota play key roles in microbial food webs, as recently demonstrated (Dai et al 2021 , Petters et al 2021 ). Former studies have shown Myxococcota to be abundant in active layer samples (Inglese et al 2018 , Malard and Pearce 2018 , Romanowicz and Kling 2022 ), especially also in this site (Scheel et al 2022 ). Within the active layer, seasonally increased prokaryotic biomass could support higher predator abundances.…”
Section: Discussionmentioning
confidence: 84%
“…Bacterial predators and particularly Myxococcota play key roles in microbial food webs, as recently demonstrated (Dai et al 2021 , Petters et al 2021 ). Former studies have shown Myxococcota to be abundant in active layer samples (Inglese et al 2018 , Malard and Pearce 2018 , Romanowicz and Kling 2022 ), especially also in this site (Scheel et al 2022 ). Within the active layer, seasonally increased prokaryotic biomass could support higher predator abundances.…”
Section: Discussionmentioning
confidence: 84%
“…In the foothills of this region, mountain glaciations have produced land surfaces of different ages from relatively younger (∼14,000 years BP since last glaciation) to relatively older (>250,000 years BP since last glaciation; Hamilton, 2003). Soil cores were collected from within the permafrost layer (at 85 cm below the surface and ∼10–30 cm below the maximum summer thaw depth; see Romanowicz & Kling, 2022) of Imnavait Creek wet sedge (wet sedge) and Toolik Lake tussock tundra (tussock tundra) soils, which represent the dominant landscape ages and vegetation types of the low Arctic (Figure S1 and Table S1 in Supporting Information ; Ping et al., 1998; Trusiak et al., 2018a; Walker et al., 2005; Walker & Maier, 2008). DOC leached from these soils has a range of chemical compositions and ages (Bowen et al., 2020b; Trusiak et al., 2018a; Ward et al., 2017).…”
Section: Methodsmentioning
confidence: 99%